Problem-Based Learning Model in Elementary School Students: Learning Activity and Learning Outcomes - Krisdianto, Indun; Sudarmiani, Sudarmiani; Nugraha, Nurhadji (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study investigates the effectiveness of the Problem-Based Learning (PBL) model in improving learning activity and learning outcomes of elementary school students in IPAS (Science and Social Studies) learning within the context of the Merdeka Curriculum implementation.Methodology: A quantitative approach was employed using a quasi-experimental posttest non-equivalent control group design. The participants consisted of 22 third-grade students at SDN 02 Nambangan Lor, Madiun City, divided into an experimental class (n = 11) taught using the PBL model and a control class (n = 11) taught using a traditional learning model. Data were collected through learning activity observation sheets and learning outcome tests, then analyzed using descriptive statistics and independent sample t-tests with a significance level of 0.05.Main Findings: The results show that students in the experimental class demonstrated significantly higher learning activity and learning outcomes compared to those in the control class. The independent sample t-test revealed a significant difference in learning activity (t = 4.129, p < 0.05) and learning outcomes (t = 5.744, p < 0.05) between the two groups. These findings indicate that the PBL model is more effective than traditional learning in fostering active student participation and improving academic achievement.Novelty/Originality of this study: This study provides empirical evidence supporting the integration of Problem-Based Learning as an instructional strategy to enhance the quality of IPAS learning in elementary schools, particularly in alignment with the student-centered principles of the Merdeka Curriculum.